(untitled) (Prostor, 2024)
The challenge in obtaining objective parameters for evaluating the aesthetic appeal of buildings is what we try to explain through a case study, presenting a pioneering methodology that can be applied and adapted to different architectural styles. Our focus is on a substantial investigation of Romanian Orthodox churches in the Wallachia region, which exhibit striking similarities from their early stylistic developments in the 16th century to contemporary examples. By examining the geometric relationships within their interior spaces, we aim to derive objective insights that enable an alternative classification. This classification, in turn, helps us measure the emotional impact these spaces have on users or visitors, influencing emotions based on spatial proportions. Through these relationships, we can evaluate the importance of different buildings of the same category, classify them and, objectively explain their differences. Applying the findings of this study, along with specific variables, to other architectural contexts allows us to address user preferences more effectively to enhance architectural designs by improving comfort and the quality of life.